2016
DOI: 10.2147/ijwh.s88904
|View full text |Cite
|
Sign up to set email alerts
|

Profile of follitropin alpha/lutropin alpha combination for the stimulation of follicular development in women with severe luteinizing hormone and follicle-stimulating hormone deficiency

Abstract: A severe gonadotropin deficiency together with chronic estradiol deficiency leading to amenorrhea characterizes patients suffering from hypogonadotropic hypogonadism. Administration of both follicle-stimulating hormone (FSH) and luteinizing hormone (LH) to these patients has been shown to be essential in achieving successful stimulation of follicular development, ovulation, and rescue of fertility. In recent years, the availability of both recombinant FSH (rFSH) and recombinant LH (rLH) has provided a new ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 102 publications
(110 reference statements)
0
10
0
Order By: Relevance
“…In most countries, r-hFSH/r-hLH is indicated for the stimulation of follicular development in adult women with severe LH and FSH deficiency [ 2 , 5 ]. It is also indicated for use in patients with sub-optimal response after controlled ovarian stimulation undergoing assisted reproductive technologies (ART) in Mexico, Russia, and Ukraine.…”
Section: Introductionmentioning
confidence: 99%
“…In most countries, r-hFSH/r-hLH is indicated for the stimulation of follicular development in adult women with severe LH and FSH deficiency [ 2 , 5 ]. It is also indicated for use in patients with sub-optimal response after controlled ovarian stimulation undergoing assisted reproductive technologies (ART) in Mexico, Russia, and Ukraine.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it is equally important not to exceed the proper daily dose to avoid the so called ‘ceiling effect’. Published data suggest that the ideal LH daily dose should be 75 IU ( 15 , 17 , 18 ). However, these recommendations cannot be applied to all patients and under all treatment circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the group that received 225 IU rLH had a smaller number of growing follicles when compared with the group who received 75 IU rLH. This could suggest an LH ceiling effect, whereby some secondary follicles underwent atresia due to their high sensitivity to LH ( 17 ). Loumaye et al confirmed this effect showing that rLH when administered alone can trigger follicular growth arrest ( 18 ).…”
Section: Women With Depleted Basal Fsh and Lh Serum Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore LH plays a role in optimal follicular response and patients with low endogenous LH levels as in hypogonadotropic hypogonadism may benefit from rLH supplementation [16] [17].…”
Section: Discussionmentioning
confidence: 99%